Lateral Instability of Castellated Beams - Pattanayak, Umesh C.; Chesson, Jr. (Engineering Journal, 1974)
The study reported herein deals with the lateral instability analysis of castellated beams using the principle of minimum potential energy. Several experiments available from the literature provide information for selecting the deformed configuration which satisfies the conditions of both statics and geometry at the boundary; certain idealizations are then made to characterize the geometrical features necessary for the purpose of analysis. The sets of Eqs. (12) and (14) provide the solution for lateral buckling of castellated beams under uniform load and concentrated load at mid-span, respectively. These equations include the solution for the external load when it is applied on the top flange, at the middepth longitudinal axis, or suspended from the bottom flange. It is observed that the critical load depends upon several parameters representing the geometrical features of castellated beams. In the case of commercially available products, the relations between critical loads and the governing parameters can be plotted with the help of the derived formulas for convenient use in practical design.